TELECOM TANGLED WIRES - Ahmad, Zubair (International Journal of Research -GRANTHAALAYAH, 2021)
In India upto 1995 landline telephones are using by people of India. The connection of telephone is very limited to the general public and many times user approaches to the M.P., M.L.A. for himself to write a letter in favour for them to get the permission for the telephone connection. In August 1995, then Chief Minister of West Bengal, Jyoti Basu made the first mobile phone call in India to then Union Telecom Minister Sukhram. Sixteen years later 4G services were launched in Kolkata in 2012. When the mobile network launches in India there are two companies who work separately in the field named Usha & Essar.